STUDI SEKTOR PERTANIAN BERBASIS EKONOMI KERAKYATAN - Effendy Faza, Rayhan; Widiyanti, Dwi Retno (Journal of Development Economic and Social Studies, 2022)
The agricultural sector is an important sector in the country's economy. Based on Gross Domestic Product (GDP), agriculture is one of the sectors that contributes to large employment opportunities so that the proportion of GDP is large. However, this sector faces a big challenge, namely agricultural liberalization which causes the farmer surplus to fall. Agricultural liberalization is not in accordance with the principle of people's economy which aims to improve people's economic welfare. This study aims to determine the implementation of the agricultural sector on the concept of a populist economy. The method used in this research is literature study with secondary data sources. The results of the study indicate that the implementation of the agricultural sector in the populist system has been carried out since President Soekarno until now President Joko Widodo. However, the policy was not optimally implemented due to the challenges faced such as liberalization of the agricultural sector, inadequate infrastructure and the program was stopped or discontinued. Some of the strategies implemented are holding of food SOEs, setting prices on commodities, developing cooperatives and agrarian reform.